Pendapatan Usahatani Jagung di Subak Lanyah Delod, Desa Tangguntiti Kecamatan Selemadeg Timur, Kabupaten Tabanan - Ni Gst.Ag Eka Martiningsih; I Made Tamba; Matias Sion (Fakultas Pertanian dan Bisnis Universitas Mahasaraswati Denpasar, 2023)
The purpose of this study was to analyze the income from corn farming and to determine the efficiency of corn farming in Subak Lanyah Delod, Tabanan Regency. The sampling technique in this study used the purposive sampling method or deliberate sampling. The data analysis method used in this study is income analysis by determining costs and revenues. Farming efficiency is sought by the R/C formula. The results of this study show that maize farming income in Subak Lanyah Delod per harvest season is Rp. 13.723.630 The average land area is 73.2 acres and has an R/C Ratio of 3,66. From the results of the calculation of R/C above, it can be explained that corn farming has an excess value of> 1, this indicates that corn farming is efficient to work on.